The prevalence of occupational accidents and diseases among 112 emergency medical workers and factors affecting it - Kara, Kevser Tuncer; Bulut, Irem; Gurgoze, Ramazan; Deveci, S. Erhan; Oguzoncul, A. Ferdane (Ondokuz Mayis Universitesi, 2022)
Occupational health has been defined by the World Health Organization (WHO) as employees in all professions have complete physical, mental, and social well-being and maintain and develop this well-being. This study aimed to determine the prevalence of work-related risks, work-related diseases, occupational accidents, and diseases faced by 112 emergency medical workers and factors affecting it. This descriptive, cross-sectional study included 415 health personnel working in 112 emergency medical services in Elazig Province. It was found that 74.7%, 21.2%, and 6.3% of participants, throughout their professional life, have experienced at least one of the work-related risks, occupational accidents, and diseases, respectively. Female employees experienced more work-related diseases (p<0.01), work-related risks (p<0.01), and occupational accidents (p<0.01) than males. Being female was identified as a risk factor, and training on occupational health and safety issues was a protective factor. © 2022 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: 112 EMW; occupational accident; occupational disease; occupational health; work-related risk